(3GdUGOM hGdHGZes - (3eMeO Hf eMeO Hf UGdM GdYHGSj, fXGe GdOjf CHh jYdj, GHf GdgHGQjI , J (B509 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj MHGfj HGdCUZQjf GdbdH hGddSGf s
(3BNQgG (B:s
(3Ef GdaNGQ hGdYdG EQKc ef Ohf GdedG Je GdcJGH fSNoG HMeO Gddg s
(3HChdgG Jedc CMeO Hf CMeO Hf GdUGFZ GdMfajs
(3hcJH HLhGQg HNW eNJda GHf GdUGFZ gPG ef YdeGA GdbQf GdKGefs
(3JJab aj ChdgG hBNQgG eY GdfSNI GdKGfjI eY GNJdGa aj HYV GdCdaGXs
(3fSNI SGOSI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B23 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B225s
Keywords: (3GdCOHs